Dual band printed quasi-yagi antenna for RFID and WLAN applications - Ullah, M.H.; Wan Mahadi, W.N.L.; Latef, T.A.; Islam, M.T.; Uddin, M.J.; Ahsan, M.R. (John Wiley & Sons, 2015)
In this letter, a new dual band quasi-Yagi antenna is presented for Radio Frequency Identification (RFID) reader and Wireless Local Area Network (WLAN). The proposed antenna is comprised of 0.17λ × 0.13λ radiating patch and reduced ground plane. The proposed antenna is fabricated on a custom made copper laminated 1.25-mm thick dielectric substrate (εr=4.5). Measurement results show that 27.78% and 23.4% bandwidths with maximum gains of 4.95 dBi and 7.26 dBi in lower and upper band, respectively. Configuration of driving elements, director, and the pairs of folded arm between excitation point and the driven element was optimized that reduces the length of driving poles significantly. Nearly, stable radiation characteristics with proper impedance matching make the proposed antenna appropriate for universal portable RFID reader with WLAN functionality.